Computational design of resonant phononic crystal for aperiodic stress wave attenuation. Issue 2 (22nd July 2020) - Luo, Chengcheng; Ning, Shaowu; Liu, Zhanli; Li, Xiang; Zhuang, Zhuo
Abstract : Purpose: This paper aims to propose a design method for attenuating stress waves pressure using soft matrix embedded with particles. Design/methodology/approach: Based on the phononic crystal theory, the particle composed of hard core and soft coating can form a spring oscillator structure. When the frequency of the wave is close to the resonance frequency of the spring oscillator, it can cause the resonance of the particle and absorb a lot of energy. In this paper, the resonant phononic crystal with three phases, namely, matrix, particle core and coating, is computationally designed to effectively mitigate the stress wave with aperiodic waveform. Findings: The relationship between the center frequency and width of the bandgap and the geometric and physical parameters of particle core are discussed in detail, and the trend of influence is analyzed and explained by a spring oscillator model. Increasing the radius of hard core could effectively enhance the bandgap width, thus enhancing the effect of stress wave attenuation. In addition, it is found that when the wave is in the bandgap, adding viscosity into the matrix will not further enhance the stress attenuation effect, but will make the stress attenuation effect of the material worse because of the competition between viscous dissipation mechanism and resonance mechanism. Research limitations/implications: This study will provide a reference for the design of stress wave protection materials with general stress waves. Originality/value: This study proposes a design method for attenuating stress waves pressure using soft matrix embedded with particles.